Iron deficiency in children - causes, consequences, treatment - review of the literature - Dziewierz, Anna; Dziewierz, Paulina; Pietrusińska, Patrycja; Sadowska, Aleksandra; Welkier, Aleksandra; Sobiński, Adam; Miśkiewicz, Joanna; Dudek, Aleksandra; Moder, Jakub; Kwaśniewska, Paula; Śliwa-Tytko, Patrycja (Journal of Education, Health and Sport, 2025)
Iron deficiency (ID) is one of the most widespread nutritional deficiencies. Children belong to one of the high-risk groups for iron insufficiency, due to the increased requirement during the period of intensive growth. ID can have unfavorable effects on brain development and the ability to learn. It can also impair the development of cognitive functions in children. Iron deficiency occurs as a result of insufficient iron intake from the diet, malabsorption associated with gastrointestinal diseases, increased requirement e.g. due to frequent bleeding. Iron is present in food in two forms: haem and non-haem. The haem form is found in animal products and is better absorbed. Early detection is essential to prevent the effects of insufficiency. The most frequently used test to diagnose iron deficiency is the ferritin level. However, a complete blood count is recommended to determine the overall condition of the body. When ID impairs the function of red blood cells, anaemia occurs. To prevent iron deficiency, women should be taken care of during pregnancy by introducing appropriate supplementation. Nutrition plans that incorporate iron-fortified foods in high-risk ID areas are also becoming more prevalent. Treatment of the insufficiency involves supplementation by oral or intravenous administration or through blood transfusions. In each method, a well-balanced diet containing foods rich in highly absorbable forms of iron is essential.